2020
DOI: 10.1093/mnras/staa2392
|View full text |Cite
|
Sign up to set email alerts
|

Stellar-mass black holes in young massive and open stellar clusters – IV. Updated stellar-evolutionary and black hole spin models and comparisons with the LIGO-Virgo O1/O2 merger-event data

Abstract: I present a set of long-term, direct, relativistic many-body computations of model dense stellar clusters with up-to-date stellar-evolutionary, supernova (SN), and remnant natal-kick models, including pair instability and pulsation pair instability supernova (PSN and PPSN), using an updated version of ${\tt NBODY7}$ N-body simulation program. The N-body model also includes stellar evolution-based natal spins of BHs and treatments of binary black hole (BBH) mergers based on numerical relativity. These, for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 230 publications
1
47
0
1
Order By: Relevance
“…We also find that, since GW radiation is efficient in reducing the eccentricity of merging binaries, sub-hertz detectors such as the proposed DECIGO detector (Kawamura et al 2011) will be crucial to understand the contribution of GCs to the merger rate (see also . Note, that due to limitations of the CMC code, we are not including effects from weak secular interactions that otherwise have been shown to both increase the BBH merger rate and give rise to dynamics similar to those of eKL interactions, including orbital spin flips and eccentricity excitations , 2020Samsing et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also find that, since GW radiation is efficient in reducing the eccentricity of merging binaries, sub-hertz detectors such as the proposed DECIGO detector (Kawamura et al 2011) will be crucial to understand the contribution of GCs to the merger rate (see also . Note, that due to limitations of the CMC code, we are not including effects from weak secular interactions that otherwise have been shown to both increase the BBH merger rate and give rise to dynamics similar to those of eKL interactions, including orbital spin flips and eccentricity excitations , 2020Samsing et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There have been many proposed formation channels, both in dense stellar environments and in isolation. These include isolated binary stellar evolution of two massive stars either through common-envelope evolution (Dominik et al 2012(Dominik et al , 2013Belczynski et al 2016aBelczynski et al , 2016bSpera et al 2019), chemically homogeneous evolution of close binaries (de Mink & Mandel 2016; Mandel & de Mink 2016), or catalyzed by flyby perturbations in the field (Michaely & Perets 2019, 2020, or dynamical assembly in dense stellar environments, including young and open star clusters (Banerjee 2017(Banerjee , 2018a(Banerjee , 2018b(Banerjee , 2020Di Carlo et al 2019;Santoliquido et al 2020) Hamers et al 2018;Hoang et al 2018;Fragione et al 2019a;Rasskazov & Kocsis 2019;Stephan et al 2019), and in active galactic nucleus (AGN) (Bartos et al 2017;Stone et al 2017;Tagawa et al 2018Tagawa et al , 2020aTagawa et al , 2020bMcKernan et al 2020). Another proposed scenario involves primordial BHs merging in the halos of galaxies (e.g., Bird et al 2016).…”
mentioning
confidence: 99%
“…Ultimately (depending on the host cluster's escape velocity), these binary BHs (BBHs) are either dynamically ejected from their host cluster through gravitational recoil or merge inside their host cluster through GW inspiral. Recent studies have shown that YSCs (e.g., Ziosi et al 2014;Di Carlo et al 2019a;Banerjee 2021) and old GCs (e.g., Rodriguez & Loeb 2018;Antonini & Gieles 2020;Kremer et al 2020b) may contribute comparably to the overall BBH merger rate.…”
Section: Introductionmentioning
confidence: 99%
“…Several channels can lead to the formation of binary black holes (BBHs): Pairing of primordial black holes (e.g., [12][13][14]), binary star evolution through common envelope (e.g., ) or via homogeneous mixing (e.g., [39][40][41][42]), dynamical processes in triples (e.g., [43][44][45][46][47]), young/open star clusters (YSCs, e.g., [48][49][50][51][52][53][54][55][56][57][58]), globular clusters (GCs, e.g., [59][60][61][62][63][64][65][66][67][68]), nuclear star clusters (NSCs, e.g., [69][70][71][72][73][74][75][76][77]) and AGN disks (e.g., [78][79][80][81][82][83]).…”
Section: Introductionmentioning
confidence: 99%